Gone to Pot – A Review of the Association between Cannabis and Psychosis - Radhakrishnan, Rajiv; Wilkinson, Samuel T.; D’Souza, Deepak Cyril (Frontiers in Psychiatry, 2014)
Cannabis is the most commonly used illicit drug worldwide, with approximately 5 million daily users worldwide. Emerging evidence supports a number of associations between cannabis and psychosis/psychotic disorders, including schizophrenia. These associations based on case-studies, surveys, epidemiological studies, and experimental studies indicate that cannabinoids can produce acute, transient effects; acute, persistent effects as well as delayed, persistent effects that recapitulate the psychopathology and psychophysiology seen in psychotic illness such as schizophrenia. Acute exposure to both cannabis and synthetic cannabinoids (Spice/ K2) can produce a full range of transient psychotomimetic symptoms, cognitive deficits, and psychophysiological abnormalities that bear a striking resemblance to symptoms of schizophrenia. In individuals with an established psychotic disorder, cannabinoids can exacerbate symptoms, trigger relapse, and have negative consequences on the course of the illness. Several factors appear to moderate these associations, including family history, genetic factors, history of childhood abuse, and the age at onset of cannabis use. Exposure to cannabinoids in adolescence confers a higher risk for psychosis outcomes in later life and the risk is dose-related. Individuals with polymorphisms of COMT and AKT1 genes may be at increased risk for psychotic disorders in association with cannabinoids, as are individuals with a family history of psychotic disorders or a history of childhood trauma. The relationship between cannabis and schizophrenia fulfills many but not all of the standard criteria for causality, including temporality, biological gradient, biological plausibility, experimental evidence, consistency, and coherence. At the present time, the evidence indicates that cannabis may be a “component cause” in the emergence of psychosis, and warrants serious consideration from the point of view of public health policy.